Reconstructing the Meaning of Justice in the Practice of Taʿzir: The Perspective of Equality Before the Law at Miftakhurrosyidin Islamic Boarding School - Asyharul Muala; Kurnia Laili Khamida (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
Indonesia, as a rule-of-law state, is obligated to uphold the principle of equality before the law, as enshrined in Article 27 paragraph (1) of the 1945 Constitution. This study seeks to examine the construction of taʿzir practices at Pondok Pesantren Miftakhurrosyidin Temanggung and to critically analyze how the principle of equality before the law is interpreted and implemented within these practices. Employing a qualitative approach, this research is conducted in a natural setting to obtain a comprehensive and in-depth understanding of the mechanisms underlying the implementation of taʿzir. As a field study, data are gathered through direct observation and engagement with the lived practices in the pesantren, particularly concerning the application of legal equality in disciplinary measures. The findings indicate that the imposition of taʿzir follows an internal adjudicative process informed by a conception of justice aligned with Aristotelian thought, which emphasizes proportionality rather than rigid uniformity. In this framework, justice is realized through the allocation of rights and sanctions in accordance with the specific context and social roles of individuals, allowing for both equal and differentiated treatment where appropriate